Improving Competency Hosted Skills through Think-Pair-Share Cooperative Learning Models in Class XI Science Students of SMA Negeri 1 Ratahan - Karim, Ridwan; Mandang, Ferry Hertog; Luntungan, Grace; Rotty, Viktory Nicodemus Joufree (AIBPM Publisher, 2020)
The purpose of this study is to describe the Competency Hosted Skills through Think Pair Share Cooperative Learning Models of Class XI Students in SMA Negeri 1 Ratahan. This research was conducted at Ratahan State High School 1 in class XI 2019/2020 Academic Year consisting of 37 students. The method used in this research is classroom action research. The average value is 68 in cycle I. Meanwhile, the average value of class XI in the second cycle reached 79.9. These results indicate an increase of 8 or 11% from cycle I to cycle II. This increase proves the success of hosted learning through the cooperative pattern of think pair share. Behavior of class XI students of SMA Negeri 1 Ratahan has changed for the better after participating in the learning of hosted skills through a pattern of think-pair-share cooperation. Schools should further maximize the function of multimedia spaces in schools to support the learning of Indonesian language